In-vitro evaluation of the effects of insertion and sterilization procedures on the mechanical and surface characteristics of mini screws - Nazan Küçükkeleş; Mustafa Ateş; Yasemin Bahar Acar; Civan Aved Hergel (Istanbul University, 2019)
PurposeThe aim of the present study was to investigate the effects of insertion andsterilization on primary stability and to examine the mechanical and surfacecharacteristics of mini screws.Materials and methods140 miniscrews (70 Dual-Top; 70 Ortho-Easy) were divided into 3 groups. Group1: control group, 10 miniscrews of each brand, evaluated without any primaryprocedure. Group 2: 30 miniscrews of each brand, each inserted into the sawboneonce, then sterilized and tested. Group 3: 30 miniscrews of each brand, eachinserted into the sawbone twice, sterilized after each insertion and then tested. Theminiscrews were evaluated for changes in primary stability, mechanical and surfacecharacteristics with scanning electron microscopy (SEM) analysis, torsion tests,maximum insertion-removal torques and vertical-horizontal pull out strength tests.ResultsThe maximum insertion torque values of the unused miniscrews (Group 1) werefound to be significantly higher than those of the reused (Groups 2, 3) mini screws(p<0.05). Removal torque, vertical-horizontal pull-out strength and torsionalstrength value changes were found to be statistically insignificant. In SEM analysis,wear and atrophy were seen on the threads of used miniscrews especially in theapical region and the oxide layer was seen to have disappeared from some regionsof the coated miniscrews.ConclusionAlthough wear and atrophy were detected in SEM analysis of used miniscrews,the overall primary stability and fracture torque resistance tests did not show anysignificant changes after the first and second insertion and sterilization procedures.